Impacts of Environment-Related Technology, Structural Change, and Globalization on Greenhouse Gas Emissions: Evidence from Top Twenty Emitter Countries - Altaee, Hatem Hatef Abdulkadhim; Azeez, Saya Jamal (International Journal of Energy Economics and Policy, 2023)
The issues of environmental degradation, climate change, and rising temperatures are a real and growing concern for humanity at the level of individuals, groups, and societies. Reducing greenhouse gas is an important element for nations to achieve their ambitious climate-resilient growth goals. The purpose of this research is to investigate the impact of environment-related technology, structural change, income, and globalization on greenhouse gas (GHG) emissions in the top twenty emitter countries from 1997 to 2019. To this end, this study has applied the new and widely used method of moment quantile regression (MMQREG) to permit the estimation of relationships across the distribution of an outcome. In order to test the reliability of the benchmark estimation results, this article uses three different methods for robust testing, the PCSE, FGLS and the linear regression with Driscoll–Kraay standard errors. The main findings of this paper show that environment-related technology, structural change, and globalization helps to boost ecological quality. Moreover, there is strong evidence on the existence of an N shape EKC. Based on the findings of this paper, governments should encourage investment in environment related technology and post the transition to services-based economies.